2021
DOI: 10.1002/etc.5051
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and Ecotoxicity of Lead in Soil: Implications for Setting Ecological Soil Quality Standards

Abstract: Ecological soil quality standards for lead (Pb) that account for soil Pb bioavailability have not yet been derived. We derived such standards based on specific studies of the long-term bioavailability and toxicity of Pb to soil organisms and a compilation of field data on the bioaccumulation of Pb in earthworms. Toxicity thresholds of Pb to plants, invertebrates, or microorganisms vary over more than 2 orders of magnitude, and the lowest values overlap with the range in natural Pb background concentrations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 47 publications
1
7
0
Order By: Relevance
“…On the other hand, Oorts et al attempted to quantify the role of Pb 2+ bioavailability on ecological soil quality standards and found that soils freshly spiked with Pb 2+ salts similar to those in perovskite PV exhibited higher Pb bioavailability and lower toxic thresholds than long-term aged and leached equivalents . The results of the comparative toxicity tests of the study indicate that Pb soil screening thresholds could be increased by up to a factor of 4 compared to thresholds determined using freshly spiked soils.…”
Section: Resultsmentioning
confidence: 85%
“…On the other hand, Oorts et al attempted to quantify the role of Pb 2+ bioavailability on ecological soil quality standards and found that soils freshly spiked with Pb 2+ salts similar to those in perovskite PV exhibited higher Pb bioavailability and lower toxic thresholds than long-term aged and leached equivalents . The results of the comparative toxicity tests of the study indicate that Pb soil screening thresholds could be increased by up to a factor of 4 compared to thresholds determined using freshly spiked soils.…”
Section: Resultsmentioning
confidence: 85%
“…Accumulating evidence indicates that the mechanism underlying Pb toxicity involves elevated oxidative stress due to ROS production and antioxidant capacity depletion [ 42 , 43 ]. In this present experiment, we observed that the brains of rats pretreated with EGCG before ischemic injury had lower Pb concentrations than did those from untreated ischemic injury rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, the difficulties in studying the HM partitioning between the soil solid phase and solution remain for the real soil-to-solution ratios under field conditions. In particular, the latter include the addition of soluble HM salts in laboratory adsorption and ecotoxicological experiments that ignore the longterm processes of metal binding and a decrease in their bioavailability, characteristic of the field conditions [61,65,75,87,93]. The efforts to model the ageing process depending on soil properties and duration of interaction are necessary [110].…”
Section: Problems and Prospectsmentioning
confidence: 99%